Identifying Type 2 Diabetic Brains by Investigating Disease-Related Structural Changes in Magnetic Resonance Imaging - Chen, Yuna; Pan, Yongsheng; Kang, Shangyu; Lu, Junshen; Tan, Xin; Liang, Yi; Lyu, Wenjiao; Li, Yifan; Huang, Haoming; Qin, Chunhong; Zhu, Zhangzhi; Li, Saimei; et al. (Frontiers in Neuroscience, 2021)
Diabetes with high blood glucose levels may damage the brain nerves and thus increase the risk of dementia. Previous studies have shown that dementia can be reflected in altered brain structure, facilitating computer-aided diagnosis of brain diseases based on structural magnetic resonance (MR) images. However, the diabetes mellitus (DM)-mediated changes in the brain structures have not yet been studied, and only a few studies have focused on the use of brain MR images for automated diagnosis of DM. Hence, identifying MRI biomarkers is essential to evaluate the association between changes in brain structure and diabetic mellitus as well as cognitive impairment. The present study aimed to investigate four methods to extract features from MR images, characterize imaging biomarkers, and identify subjects with diabetes and cognitive impairment.